Coagulation of peptides and proteins produced by Microcystis aeruginosa: Interaction mechanisms and the effect of Fe-peptide/protein complexes formation - Pivokonsky, Martin; Safarikova, Jana; Bubakova, Petra; Pivokonska, Lenka (Water research, 2012)
This paper focuses on elucidation of the mechanisms involved in the coagulation of peptides and proteins contained in cellular organic matter (COM) of cyanobacterium Microcystis aeruginosa by ferric coagulant. Furthermore, coagulation inhibition due to the formation of Fe-peptide/protein surface complexes was evaluated. The results of coagulation testing imply that removability of peptides and proteins is highly dependent on pH value which determines charge characteristics of coagulation system compounds and therefore the mechanisms of interactions between them. The highest peptide/protein removal was obtained in the pH range of 4-6 owing to charge neutralization of peptide/protein negative surface by positively charged hydrolysis products of ferric coagulant. At low COM/Fe ratio (COM/Fe <0.33), adsorption of peptides/proteins onto ferric oxide-hydroxide particles, described as electrostatic patch model, enables the coagulation at pH 6-8. On the contrary, steric stabilization reduces coagulation at pH 6-8 if the ratio COM/Fe is high (COM/Fe >0.33). Coagulation of peptides and proteins is disturbed at pH 6-7 as a consequence of Fe-peptide/protein complexes formation. The maximum ability of peptides/proteins to form soluble complexes with Fe was found just at pH 6, when peptides/proteins bind 1.38 mmol Fe per 1 g of peptide/protein DOC. Complex forming peptides and proteins of relative molecular weights of 1, 2.8, 6, 8, 8.5, 10 and 52 kDa were isolated by affinity chromatography.
Keywords: Peptides; železité sloučeniny; peptidy; proteiny; Microcystis; flokulace; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; Flocculation; Ferric Compounds; Proteins